The role of Law 04/10 in promoting professional sports in Algeria - Brahimi, tarek (sports creativity, 2025)
The rule of law 04/10 in the embodiment of professional sports in Algeria. Summary Algeria is trying to experience professionalism in general and in the field of professional football in particular, which we will try to focus on through this paper; as, on the one hand, the development of football for being the most popular sport in Algeria. On the other hand, requiring the Federal Algerian Football Club professionalism specific to them in 2011 as the deadline for the implementation as approved by the Federal International Football Association (FIFA) under penalty of not to participate in international competitions and the World. And although Algeria has opened the field of professionalism in 1995 under Ordinance No. 95/09 and confirmed this trend under the law 04/10, but the clubs until today (year 2010) for any period of fifteen years can not enter into the professional ranks, but more than that are unable to go to a professional system, which raises the question of the effectiveness of law 04/10 and its role in the realization of policy in the field of professional football in Algeria?.